Mature cystic teratoma with malignant transformation: A rare case report (Indian Journal of Case Reports, 2024)
Mature cystic teratomas (MCTs) are common benign ovarian tumors of the reproductive age group. Malignant transformation of MCT occurs in 1.5–2% of the cases. Here, we report the case of a 52-year-old female who presented with abdominal distension and weight loss for 6 months. Her tumor markers were elevated and the computed tomography abdomen revealed a large complex solid cystic abdominopelvic mass. On gross examination, an ovarian with a breached capsule was received, and the cut section showed the presence of hair, bony, and sebaceous elements in the solid component. On histopathological examination, the case was reported as moderately differentiated squamous cell carcinoma arising in an MCT. Early detection, complete resection, and meticulous histopathological examination should be done to deliver timely management and prolong survival in such patients.